2012
DOI: 10.1016/j.soilbio.2012.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Influence of litter chemistry and stoichiometry on glucan depolymerization during decomposition of beech (Fagus sylvatica L.) litter

Abstract: Glucans like cellulose and starch are a major source of carbon for decomposer food webs, especially during early- and intermediate-stages of decomposition. Litter quality has previously been suggested to notably influence decomposition processes as it determines the decomposability of organic material and the nutrient availability to the decomposer community. To study the impact of chemical and elemental composition of resources on glucan decomposition, a laboratory experiment was carried out using beech (Fagu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 46 publications
4
17
0
Order By: Relevance
“…However, it is interesting that the Bogo pasture had the lowest overall C/N ratio and the highest overall GH48 abundance; likewise, the Bogo woodlands had the lowest C/N ratio and the highest GH48 abundance among woodlands (46). This pattern agrees with data from studies showing that higher C/N ratios are negatively correlated with extracellular hydrolytic enzyme activity during litter decomposition (69).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, it is interesting that the Bogo pasture had the lowest overall C/N ratio and the highest overall GH48 abundance; likewise, the Bogo woodlands had the lowest C/N ratio and the highest GH48 abundance among woodlands (46). This pattern agrees with data from studies showing that higher C/N ratios are negatively correlated with extracellular hydrolytic enzyme activity during litter decomposition (69).…”
Section: Discussionsupporting
confidence: 85%
“…2A). The C/N ratio is thought to influence litter C availability, and a high C/N ratio has a negative effect on extracellular hydrolytic enzymes during litter decomposition (69,70). It is not surprising, therefore, that the C/N ratio was one of the vectors with the strongest correlations to the main PCO axis and was more important than the levels of the organic soil carbon fractions themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Data represents two replicates at each sampling date i.e. days 8, 14, 21, 28, 35 and 43 LSD states for least significant differences, nd for not determined levels of glucan, suggesting that soil microorganisms use glucan (cellulose) as the preferred substrate irrespective of the type of residue (Leitner et al 2012) (Fig. 5a), and that enzyme production was responsive to substrate availability (Leinweber et al 2008).…”
Section: Dynamics Of Residue Chemical Features During Decompositionmentioning
confidence: 99%
“…In accordance with other studies (Bongiovanni and Lobartini, 2006), the cultivation of wheat had an overall detrimental effect on all of the organic C pools examined. The major depletion observed at 0-10 cm of the P-C soil was likely due to higher microbial biomass content and activity coupled with greater availability of N (Leitner et al, 2012;Zotarelli et al, 2012).…”
Section: Sampling Depth (Cm)mentioning
confidence: 96%
“…In the P-C soil, the presence of perennial legume may have favoured the continuous supply of the more accessible pools of organic carbon, i.e., LFOM and WSOC which, coupled with a higher availability of N, might have preferentially led soil microorganisms to degrade the more labile carbon instead of ligneous recalcitrant carbon, thus enhancing soil in humic fraction (Leitner et al, 2012). Indeed, in our study, the P-C soil always showed lower o-DPO activity than that in the A-C soil (Table 3).…”
Section: Sampling Depth (Cm)mentioning
confidence: 99%